American housewife ebook Stories. - Ellis, Helen (2016)
NATIONAL BESTSELLER • “A raucous, whip-smart collection of stories featuring retro-feminist ladies who lunch.” — Elle Meet the women of American Housewife . They wear lipstick, pearls, and sunscreen, even when it’s cloudy. They casserole. They pinwheel. And then they kill a party crasher, carefully stepping around the body to pull cookies from the oven. Taking us from a haunted pre-war Manhattan apartment building to the unique initiation ritual of a book club, these twelve delightfully demented stories are a refreshing and wicked answer to the question: “What do housewives do all day?”